Population Structure of the Red Macroalga Botryocladia occidentalis (Børgesen) Kylin (Rhodymeniaceae, Rhodymeniales) in the Gulf of Mexico Before the Deepwater Horizon Oil Spill - Venera-Pontón, Dagoberto E.; Schmidt, William E.; Fredericq, Suzanne (Frontiers in Marine Science, 2019)
Studies on the population structure of common widespread macroalgae in the Gulf of Mexico (GoMx) are scarce, and this knowledge gap limits our understanding on how disturbances affect the genetic diversity of macroalgae in this basin. The latter is due to the lack of a baseline that can be compared with allele frequency surveys conducted after a major disturbance such as the 2010 Deepwater Horizon oil spill (DWH), which leaked 780,000 m3 of crude oil in the vicinity of highly diverse macroalgal communities. Fortunately, quantitative assessments of the population structure pre-DWH can be accomplished for several macroalgae with dried specimens collected from research cruises conducted before 2010 in the offshore GoMx. Based on three markers (cytochrome c oxidase subunit I, COX II-III intergenic spacer, and the RuBisCO large subunit), this study reconstructed the allele frequencies pre-DWH for a GoMx-widespread macroalga, Botryocladia occidentalis, and revealed the existence of distinct populations in each of three distant regions of the GoMx: Florida Middle Grounds (FL), Campeche Banks (CB), and offshore Louisiana (LA). Population structure was assessed with exact tests of population differentiation and Analyses of Molecular Variance. FL harbored the most differentiated and genetically diverse population due to the presence and abundance of unique haplotypes. Interestingly, FL haplotypes were not closely phylogenetically related to each other and included the most divergent lineages of the entire GoMx; this phylogeographic pattern suggests a strong influence of migrants from the Caribbean on the FL population. Additionally, likelihood ratio tests with a small sample collected post-DWH indicated that the LA population underwent strong changes, showing statistically significant differences before (LA) vs. after (L2) the disaster. Whereas the LA population had affinity to CB, L2 showed a FL haplotype that, before the disaster, had never been reported in LA or CB. Such changes may not be permanent but rather a temporary response to disturbance; also, they may not necessarily be caused by the spilled oil but by other factors associated with the DWH.